Reduced Handgrip Strength in Congenital Heart Disease With Regard to the Shunt Procedure in Infancy - Müller, Jan; Röttgers, Leopold; Neidenbach, Rhoia C.; Oberhoffer, Renate; Ewert, Peter; Hager, Alfred (Frontiers in Pediatrics, 2018)
Objective: In many patients with congenital heart disease (CHD) arterial blood flow to the arms is hampered due to shunt surgery in infancy. This study investigates the handgrip strength of patients with CHD with regard to previous shunt procedures. Patients and Methods: Handgrip was evaluated in 424 patients with various CHD (189 female, age 28.1 ± 13.4years) including 63 with shunt procedures in infancy; and 123 controls (51 female, 35.6 ± 14.2years) using a Jamar dynamometer accommodated for hand size. The best of three repetitions was recorded for each side and the right-to-left hand ratio was calculated. The 63 shunted patients were grouped with regard to the side of the shunt: 14 right, 35 central and 14 left. Results: Patients with CHD, especially shunts, had significantly lower handgrip strength in the dominant hand than controls did (controls: 43.2 ± 14.8kg, CHD: 36.8 ± 14.8kg, left shunt: 33.6 ± 14.6kg, central shunt: 30.7 ± 15.2kg and right shunt 27.8 ± 13.6kg; p<.001). In controls the right hand was 8.3% stronger, comparable to patients with either no shunt or central shunt (controls: 8.3 ± 13.2%; no shunt: 7.9 ± 15.3%; central shunt: 9.5 ± 18.1% p=.820). In patients with a left shunt the right hand was 22.5 ± 17.8% stronger than the left (p=.027 compared to central) while in those with a right shunt the right hand was 2.3 ± 18.3% weaker (p=.049 compared to central). Conclusions: Shunt procedures in infancy cause reduced handgrip strength in adulthood and diminished handgrip strength of the ipsilateral site.